Efficacy of valgus osteotomy in treating nonunion of femoral neck fractures post-internal fixation - Xu, Haohao; Yang, Shenda; Zheng, Yuanyuan; Tian, Ao; Wu, Ruofei; Zhang, Xiaoyu; Mao, Yujiang (Frontiers in Surgery, 2025)
BackgroundNonunion of femoral neck fractures following internal fixation presents a significant challenge, particularly in young patients. This study evaluated the efficacy of valgus osteotomy in treating femoral neck fracture nonunion after failed internal fixation in young adults.MethodsA retrospective analysis was conducted including a total of 23 male patients with a mean age of 32.9 years, who underwent valgus osteotomy for femoral neck fracture nonunion. The procedure involved lateral closing wedge osteotomy at the subtrochanteric level, followed by fixation with a dynamic hip screw (DHS). The postoperative follow-up period exceeded one year.ResultsSignificant improvements in biomechanical parameters were observed. The mean neck-shaft angle increased from 118.91° to 139.26° (p < 0.001), whereas the Pauwels angle decreased from 62.07° to 46.91° (p < 0.001). The median Harris Hip Score improved from 63 to 96 (p < 0.001). Limb length demonstrated a trend toward improvement, increasing from a median of 73.30–74.50 cm, although this was not statistically significant (p = 0.077). Union was achieved in 22 of 23 patients, with a median healing time of 8.5 months.ConclusionValgus osteotomy is an effective treatment for femoral neck fracture nonunion in young adults, offering improved biomechanics, good union rates, and enhanced functional outcomes. This technique is a viable option for preserving the native hip joint in challenging patients.